Force Majeure or Hardship Principle In Termination of Employment During The Covid-19 Pandemic - Junaidi, Junaidi; Surahmi, Mila; Romli, Desmawaty (SASI, 2022)
Introduction: The company often uses the spread of the Covid 19 virus in Indonesia in carrying out the Termination of Employment (PHK). Force Majeure is regulated by Article 164 of Law No. 13 of 2003 on Manpower but does not regulate epidemics or diseases as force majeure. Hardship itself is not regulated, and this doctrine is not yet known in Indonesia, as evidenced by the lack of contracts implementing the hardship clause.Purposes of the Research: The purpose of this study is to provide legal protection for employees who have experienced termination of employment due to the Covid-19 pandemic based on the principle of hardship.Methods of the Research: The research method used is normative juridical or doctrinal law research. It is research that uses the approach of legislation in the governance and legal values that live in society.Results of the Research: The results of this study include two things, namely the principle of force majeure or hardship in termination of employment, Companies that terminate employment should renegotiate by delaying work or known as the hardship principle. Using the force majeure principle causes workers to be unable to carry out their obligations, namely doing work. Based on the freedom of contract, the hardship principle principle clause can continue to carry out the agreement for workers affected by Covid-19. While the second is the legal consequences of the Covid-19 pandemic on work agreements, basically, in resolving the legal consequences caused by the Covid-19 pandemic, honesty from the parties is needed. This principle is known as good faith. It greatly determines the condition of the Covid-19 pandemic in the termination of employment by the company so that the parties can renegotiate their work agreement.